Integrated Framework for Risk and Impact Assessment of Sediment Hazard on a Road Network. Issue 7 (July 2021) - Rose Santos, Johan; Varghese, Varun; Chikaraishi, Makoto; Uchida, Tatsuhiko
Road networks are highly vulnerable to risks stemming from both internal factors, such as the topological structure of the network, and external factors, such as natural disasters. The disruptions caused by these potential risk factors could result in severe physical and socio-economic losses. Therefore, understanding the impact and risk associated with road networks will be beneficial in reducing losses and helping to prepare better risk mitigation and management strategies. This study proposes an integrated approach to assess risk of sediment hazard on the road network by borrowing concepts from (a) transport vulnerability studies, (b) disaster risk assessment, and (c) spatial risk analysis and applying it to an identified vulnerable road network in Kure, Japan. The proposed risk framework holistically incorporates the processes of topological network vulnerability analysis, exposure spatial analysis, hazard occurrence probability estimation through binary logit regression, impact calculation using Monte Carlo simulation, and risk estimation. Using the recorded information on the rainfall event and sediment disaster that occurred in Hiroshima prefecture in July 2018, 12, 000 possible multi-link disruption scenarios were simulated. Spatial distribution of the risk calculations helped to identify links with high probability of disruption and high impact, that is, high-risk links. The findings of this study may support policy decisions on road risk mitigation and recovery prioritization during disaster and road infrastructure investment through risk-benefit analysis.